Oral Candidal Carriage Among Patients with Oral Squamous Cell Carcinoma: A Case-Control Study - Sankar Leena Sankari; Krishnan Mahalakshmi (Wolters Kluwer Medknow Publications, 2019)
Introduction: Etiology of oral squamous cell carcinoma is multifaceted. The established risk factors include tobacco, alcohol, and immunodeficiency states with infections gaining an importance. Candida species has been implicated in oral squamous cell carcinoma (OSCC). The present study aims at determining the prevalence of Candida species in the saliva of patients with OSCC and healthy cohorts. Materials and Methods: Unstimulated saliva was collected from patients with OSCC (n = 90) and age and sex matched healthy subjects (n = 170). The samples were inoculated onto sabouraud dextrose agar and incubated for a week. The isolates were enumerated using a colony counter. The isolates were identified using standard phenotypic methods. The significance of oral candidal carriage was calculated using chi-square test. Odds and risk ratio was calculated using pearson's chi-square test. Result: Oral candidal carriage were present in 70% of patients with oscc, while healthy cohorts had a prevalence of 20%. The oral candidal carriage among OSCC patients in comparison to healthy cohorts was highly significant. (p = 0.0001). C. albicans and non-albicans Candida were equally distributed in the OSCC group. Colony-forming units were high among patients with oscc. Significant odds and risk ratio was observed for the prevalence of Candida species among OSCC (p <0.001). Conclusion: The present study shows significant association of oral candidal carriage with OSCC in comparison to healthy cohorts.